First identification of marine anammox bacteria in Indonesia under tropical aquaculture conditions - ELMI NURHAIDAH ZAINUDDIN; GUNO GUMELAR; SHAHRUL ISMAIL; MIA MIRANTI RUSTAMA; ZULKARNAINI ZULKARNAINI (Society for Indonesian Biodiversity, 2025)
Abstract. Zainuddin EN, Gumelar G, Ismail S, Rustama MM, Zulkarnaini Z. 2025. First identification of marine anammox in Indonesia under tropical aquaculture conditions. Biodiversitas 26: 6469-6479. Marine anaerobic ammonium oxidation (anammox) bacteria offer a promising and sustainable pathway for nitrogen removal from aquatic environments, particularly in shrimp aquaculture, where nitrogen-rich waste can cause environmental problems. This study aimed to identify marine anammox bacteria (MAB) under tropical conditions in two filter bioreactors (FtBRs) operated at tropical ambient temperatures with seawater salinity of 32-33 ppt. FtBR 1 was inoculated with intensive shrimp pond sludge, while FtBR 2 received a mixture of sludge and freshwater anammox granules (Candidatus Brocadia fulgida). Microbial community profiling was performed using Illumina HiSeq sequencing targeting the V3-V4 regions of the 16S rRNA gene. Both reactors successfully enriched the marine anammox species Candidatus Scalindua wagneri, accounting for 7% (FtBR 1) and 21% (FtBR 2) of the phylum Planctomycetota. In contrast, Candidatus Brocadia fulgida failed to survive under high salinity. Notably, Xanthomarina gelatinilytica emerged as the dominant genus in both systems, suggesting its important role in the hydrolysis and mineralization of organic nitrogen originating from shrimp aquaculture sludge. MAB were successfully identified and enriched despite their low relative abundance, suggesting potential interactions with co-occurring denitrifying communities. This study represents the first documented identification of MAB in Indonesia. These findings represent the first documented presence of MAB in Indonesia from aquaculture sludge. This work provides a foundation for developing localized, low-energy nitrogen removal technologies for sustainable shrimp aquaculture in coastal regions.